Five factors for U.S. - Cuba Rapprochement - Pavel Terentev; Yulia Vlasova; Tatiana Vavichkina (Revista Científica General José María Córdova, 2024)
The article is devoted to the analysis of the five factors that may ensure the U.S. – Cuba rapprochement, such as geographical proximity, the historical experience of cooperation, existing strong economic ties between the two states, the Castro Era end implications, as well as special foreign conditions. The authors show that the USA and Cuba remain interconnected even amid the economic blockade, point out that the Cuban regime has already faced a lot of challenges in terms of economic development and public unrest, and demonstrate how new international reality fosters normalization of bilateral relations.